After the Fall : Classical Antiquity in Polish Intellectual History, 1795-1825 - Junkiert, Maciej, (Brill Research Perspectives in Humanities and Social Sciences, 2026)
This book deals with the perception of the heritage of Greco-Roman antiquity by Polish poets, historians, philologists, thinkers, translators, and scholars after 1795 when the Polish-Lithuanian Commonwealth ceased to exist. Maciej Junkiert deals with the new political and social situation brought by the loss of independence, which prompted a rethinking of Polish intellectual traditions related to antiquity. He also examines how this process was influenced by the new vision of antiquity that was emerging in German, French, British, and other European countries from the mid-18th century onwards and was linked to the development of philology, ancient history, and the history of philosophy. This new vision of antiquity, which was a result of the dominance of historicism in the humanities, involved constructing an image of the past from the perspective of contemporary needs.